Pengaruh Penambahan Pektin Kulit Pisang Kepok (Musa paradisiaca l.) Terhadap Karakteristik Fisiko-Kimia Sari Buah Naga Merah (hylocereus polyrhizus.) - Sulastri R Mustapa; Suryani Une; Siti Aisa Liputo (Universitas Negeri Gorontalo, 2022)
The research aims to determine the effect of pectin from kepok banana peel as a stabilizer in red dragon fruit juice. The research applies Completely Randomized Design (CRD) with one factor, namely concentration of addition of pectin from kepok banana peel. The research factor comprises 4 levels, namely the concentration of addition of pectin from kepok banana peel (S0-banana peel pectin for 0 g. S1-banana peel pectin for 0.5 g. S2-banana peel pectin for 1 g, and S3-banana peel pectin for 1.5 g) and each treatment is repeated three times. Observation parameters consist of total dissolved solid, viscosity, pH, stability, and organoleptic. As a result, a significant effect is observable in the parameters of total dissolved solid, viscosity. and pH. On average, the panelists prefer the color of fruit juice with the addition of 1.5 g of banana peel pectin, which is 5,77 (like). In the meantime, an increase in the concentration of the addition of kepok banana peel pectin also increases the parameter values for total soluble solid ranging from 21.40 Brix, viscosity for 3550cp, and pH for 7.27%.